Reliability assessment of waterproofing systems of buildings underground parts - Sokova, Serafima; Smirnova, Nadezhda (IOP conference series. Materials Science and Engineering, 2018)
Subject: the main question in the course of the research is the problem of the choice of optimum waterproofing system for underground parts of buildings and constructions by means of a mathematical method. Objectives: systematic approach in the solution of a task - the choice of optimum waterproofing system by means of the mathematical method (mathematical apparatus of the Boolean algebra and probability and statistical and logical methods). Materials and methods: the system "wall-base plate" including waterproofing membrane, waterproofing the key, a repair composition, fillet, concrete preparation, reinforced concrete, drainage geocomposite. Results: the mathematical logic and probability determination of waterproofing system operability at various options allows to choose optimal system. Conclusions: the effectiveness of the mathematical method is reflected in the ability to determine the preferred option of building system on the basis of the analysis of its structure.